Sistem Pendukung Keputusan Cerdas Menggunakan Metode Ant Colont Optimization (ACO) untuk Pencarian Jalur Optimum Rantai Pasok Bioenergi Berbasis Kelapa Sawit - Rina Maryani (SAFE-Network, 2022)
The concept of supply chain management in business activities is very necessary. This concept involves more than one type of company. One of the businesses that requires this concept is palm oil-based bioenergy management. The optimal path in the supply chain network is very difficult, because the product supply chain network is perishable. For that we need an intelligent decision support system model in the search for the optimal path. The purpose of this study is to determine the optimum value and to find the optimum path of the palm oil-based bioenergy supply chain. The method used in the development of the model is the ant colony optimization method, namely the shortest path method. The data processed is the distance and time of supply. The optimal path search result is 0.035. So that this research becomes a reference in determining the optimal path.